PSD-95: dynamic localization of PSD-95 and glutamate receptors at postsynaptic sites - Hell, Johannes (Henry Stewart Talks, 2022)
PSD-95, Structural proteins, PSD-95 identification and structure, Glutamatergic synapse, PSD-95 anchors glutamate receptors, Alpha-actinin anchors PSD-95, AMPAR and NMDAR, Alpha-actinin function and binding, Ca2+/CaM binding to PSD-95, Effect of Ca2+/CaM on PSD-95, Palmitoylation/depalmitoylation cycle of PSD-95, Long term depression (LTD), Homeostatic downscaling